The Screening of Antiphospholipid Antibodies in Obstetric Antiphospholipid Syndrome-Like Events: A Regional Perspective - Onen, Onder; Varol, Fusun Gulizar (Gynecology Obstetrics & Reproductive Medicine, 2020)
Objective: Obstetric antiphospholipid antibody syndrome is clinically recognized by adverse obstetric outcomes. To determine which antibody level best corresponds to the risk of these clinical outcomes is difficult. Obstetric antiphospholipid antibody syndrome-like adverse obstetric outcomes with single (n=108) and repeat (n=79) documented antiphospholipid antibody titers were evaluated. Study Design: Serum samples of 108 Obstetric antiphospholipid antibody syndrome cases and 50 healthy gestational matched controls with no history of thrombosis and congenital anomalies were subjected to testing for antiphospholipid antibodies with ELISA after the events. Of this obstetric antiphospholipid antibody syndrome group, only 79 cases underwent repeat testing within 12 weeks. Quantitative data were described by values and percentages at the levels of (>10) and (>40 U). Results: By one documented antiphospholipid test, the mean values of anticardiolipin, and anti-β2 glycoprotein1 (aβ2GP1) of obstetric antiphospholipid antibody syndrome versus controls were significantly different (p<0.001). Of 79 women who came for repeat sampling, a total number of women with persistent antiphospholipid antibody positivity was only 43 (54.43%). The number of obstetric antiphospholipid antibody syndrome cases with >40 U of antiphospholipid antibody was only 8 (18.60%). Conclusion: Not all obstetric antiphospholipid antibody syndrome associated pregnancy morbidities may own high (>40U) antiphospholipid antibody titers, but low antiphospholipid antibodies (>10U) also accompany to this clinical picture. Obstetric antiphospholipid antibody syndrome should always be taken into account clinically prior to laboratory findings. Besides, long persistence of antiphospholipid-M positivity in these placenta-mediated disorders may make sense in terms of trophoblastic damage.